Study of the stabilization process in Saccharomyces intra- and interspecific hybrids in fermentation conditions - Pérez Través, Laura (2014)
In this work, we evaluated the genetic stabilization of artificialintra- (Saccharomyces cerevisiae) and interspecific (S. cerevisiae x Saccharomyceskudriavzevii) hybrids under wine fermentative conditions. Large-scale transitions in genome sizeandgenome reorganizationswere observedduring this process. Interspecific hybrids seem to need fewer generations to reach genetic stability than intraspecific hybrids.The largest number of molecular patterns recovered among the derived cloneswas observed for intraspecific hybrids, particularly for those obtained by rare-mating.Molecular markers analyses revealed that unstable clones can suffer changes during the industrial process to obtain active dry yeast. When no changes in molecular markers and ploidy were observed after this process, no changes ingenetic composition were confirmed by comparative genome hybridization, considering the clone as a stable hybrid. According to our results, under these conditions, fermentation steps 3 and 5 (30-50 generations)suffice to obtain genetically stable interspecific and intraspecific hybrids, respectively.